Effects of chronic infection with Trichostrongylus vitrinus and immune suppression with corticosteroid on parasitological, immune and performance variables in crossbred meat lambs. (June 2015) - Blackburn, P.J.; Carmichael, I.H.; Walkden-Brown, S.W.
Highlights: First investigation of the cost of T. vitrinus in meat sheep under field conditions. T. vitrinus and corticosteroid reduced lamb weight gain by 35 and 33% respectively. Reduced weight gain was partitioned into host and parasite-mediated components. The direct effects of T. vitrinus accounted for 61% of reduced weight gain. Abstract: The effects of, and interactions between chronic Trichostrongylus vitrinus infection and immune suppression with methylprednisolone were investigated for a period of 112 days in a grazed flock of 176 crossbred meat lambs. Worm egg count of non-immune-suppressed lambs increased rapidly from days 21 to 42 post-initial infection, and then steadily declined. Infection was associated with significantly decreased fat depth, eye muscle area and cold carcase weight, and increased circulating anti- T. vitrinus IgG and IgA. Immune suppression led to sustained increases in WEC, and significantly greater worm count, liver weight, fat depth and carcase dressing percentage, and significantly reduced IgG and IgA anti- T. vitrinus titres, lymphocyte counts, adrenal weight, eye muscle area and cold carcase weight. Both infection and immune suppression were associated with significant body weight reductions. Only 39% of reduced growth rate due to infection was attributable to the host immune response to T. vitrinus .